COI barcode versus morphological identificaction of Culex (Culex) (Diptera: Culicidae) species: a case study using samples from Argentina and Brazil. - Laurito, Magdalena (2013)
Sequences of the cytochrome c oxidase subunit I (COI) mitochondrial gene from adults of 22 Culex (Culex) spe- cies from Argentina and Brazil were employed to assess species identification and to test the usefulness of COI for barcoding using the best close match (BCM) algorithm. A pairwise Kimura two-parameter distance matrix including the mean intra and interspecific distances for 71 COI barcode sequences was constructed. Of the 12 COI lineages recovered in the Neighbour-joining topology, five confirmed recognised morphological species (Cx. acharistus, Cx. chidesteri, Cx. dolosus, Cx. lygrus and Cx. saltanensis) with intraspecific divergences lower than 1.75%. Cx. bilineatus is formally resurrected from the synonymy of Cx. dolosus. Cx. maxi, Cx. surinamensis and the Coronator group species included were clustered into an unresolved lineage. The intraspecific distance of Cx. pipiens (3%) was almost twice the interspecific between it and Cx. quinquefasciatus (1.6%). Regarding the BCM criteria, the COI barcode successfully identified 69% of all species. The rest of the sequences, approximately 10%, 18% and 3%, re- mained as ambiguously, mis and unidentified, respectively. The COI barcode does not contain enough information to distinguish Culex (Cux.) species.